THE ANTIGEN-SPECIFIC CELL IN VITRO TESTS FOR POST-VACCINATION ANTIPLAGUE IMMUNITY FORMATION - A. N. Kulichenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
The possibility of post-vaccination anti-plague immunity evaluation was researched using antigen-stimulated cells tests in vitro and cytometry analysis. The object of study — the blood samples of 17 people immunised by the live plague vaccine (Yersinia pestis EV) epicutaneously. Blood taking was carried out before vaccination and after immunisation on 7 and on 21 days, in 3 and in 6 months. Intensity antigen reactivity of lymphocytes was detected by cell tests in vitro, analysing markers of early (CD45+CD3+CD25+) and late (CD45+CD3+HLA-DR+) lymphocyte activation using flow cytometry. The complex of water-soluble Y. pestis antigens and allergen — pestin PP was tested as antigen. The high stimulating potential was defined of the water-soluble antigens Y. pestis complex. It is shown that coefficient of stimulation of relative level T- lymphocytes which express receptors for IL-2 was positive for all observation times after immunisation. The coefficient of stimulation had maximum values at 21 days (56.37%) and at 3 (47.41%) months. In identifying HLADR-positive lymphocytes before vaccination, the negative coefficient of stimulation was indicated on 7 and 21 days and the positive coefficient of stimulation was indicated at 3 and at 6 months. Analysis of intensity expression of early and late lymphocyte activation markers dynamics showed the possibility and prospect of application of cellular in vitro tests for the laboratory evaluation of specific reactivity of cellular immunity in both the early (7 days) and late (6 months) periods after vaccination. The results can be the basis for developing a new algorithm for assessment of immunological effectiveness of vaccination people against plague. It is the algorithm based on the identification of lymphocyte activation markers by antigen stimulation in conditions in vitro.